ANALISIS PENGARUH WORK-FAMILY BALANCE DAN PROGRAM FAMILY FRIENDLY TERHADAP KEPUASAN KERJA Studi Kasus pada Rumah Sakit Panti Wilasa Citarum, Semarang - Paramita, Paloma; Waridin, Waridin (Benefit: Jurnal Manajemen dan Bisnis, 2006)
This research aim to test the impact of work-family balance and family friendly program to jobsatisfaction. The sample of the research are 75 nurses in Panti Wilasa Hospital by purposive sampling.Result of the research support hypotheses. First, work-family balance have positive impact to jobsatisfaction, second, family friendly program have positive impact to job satisfaction. Analyses in theresearch use multiple regression.